Effect of Electrolyte pH on Phosphate Adsorption by Soils - Bala, Parveen; Bhardwaj, S.S.; Sidhu, P.S. (Asian Journal of Chemistry, 2012)
Effect of pH phosphate adsorption by different soils was studied by varying the pH of supporting electrolytes NaCl and CaCl2. Variation in pH of NaCl did not markedly affect adsorption in all the soils. On the other hand, it decreased with pH 4 to 6 and abruptly increased above pH 7.0 when CaCl2 was used supporting electrolyte.